On the Robustness of Tests of Outliers and Functional Form - McAleer, Michael (Institutional Knowledge at Singapore Management University, 1992)
The purpose of this paper is to examine the robustness in finite samples of a test for outliers based on the maximum internally studentized residual and the RESET test for functional form misspecification. The effects of incorrect specification on the adequate detection of outliers and the presence of one or more outliers on the rejection frequencies of RESET are analysed. It is found that, ingeneral, the test for outliers does not seem to be robust to functional form misspecification, while the rejection frequencies of RESET can be reduced, sometimes dramatically, in the presence of outliers.